Respuesta :

Step-by-step explanation:

Given

w(x) = ax²+ bx +c

a=3

Soln.

w(3) = w(15) = 0

w(x) = ax² + bx + c

w(3) = a(3)² + b(3) + c ( Replace x by 3)

= 9a + 3b +c

a=3( given)

w(3) = 9(3) + 3b + c

= 27 +3b + c =0. .....(1)

w(15) = a(15)² + b(15) + c ( Replacing x by 15)

= 225a + 15b + c

a= 3(given)

w(15) = 225(3)+ 15b + c

= 675 + 15b + c = 0. .....(2)

Now solve the 2 equations by subtracting

15b + c + 675 = 0

(-) 3b + c + 27 = 0

________________

12b + 648 = 0

12b = -648

b= -648/12 = -54

Now absolute value of b = |b| = |-54| = 54.

Hope this answer helps you

ACCESS MORE